Water quality index and hydrogeochemistry of Otukpo area, Benue State, North Central Nigeria (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The research is aimed to assess the surface and groundwater quality in Otukpo area and environs, Benue State, North Eastern Nigeria. Sixteen water samples were collected from 7 boreholes, 7 hand duck wells and 2 rivers. The water samples were analysed chemically and bacteriologically using spectrophotometric, titrimetric and membrane filtration methods. Analytical results indicated that the groundwater in the area is acidic, fresh and moderately hard. The order of abundance of the cations were in Na+
Keywords: Groundwater; Water Quality Index; Domestic; Otukpo; Chemical Analysis; irrigation